Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
In the process of solving the expression x − 5 =radical 3x −11 , you will need to solve the quadratic equation x² - 13x + 36 =0
Solving radical equations
Radical equations are expression that are under the square root. For instance √x is a radical expression.
Given the equation expressed as:
x − 5 = √3x −11
Square both sides to have;
(x-5)² = (√3x −11 )²
This can be further expressed as:
(x-5)² =3x −11
Expand
x² -10x + 25 = 3x - 11
Equate to zero
x² -10x + 25 - 3x +11 = 0
x² -10x - 3x +36 = 0
x² - 13x + 36 =0
Hence in the process of solving the expression x − 5 =radical 3x −11 , you will need to solve the quadratic equation x² - 13x + 36 =0
Learn more on radical expressions here: https://brainly.com/question/6755932
#SPJ1
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.